Ekstensifikasi Subjectum Litis dalam Perselisihan Pemilu Legislatif dan Pemilihan Kepala Daerah - Agustine, Oly Viana (Mahkamah Konstitusi Republik Indonesia, 2016)
Subjectum litis in The Legislative and Regional Head Election Disputes in Indonesia has been determined in a limited manner in The legislation and The regulation of the Constitutional Court. However along with the election, there is expansion and constriction of subjectum litis. The purpose of this study was to investigate the determinant factors that cause flexibility of subjectum litis in legislative and regional head election dispute. In addition, no previous studies that examine factors associated with the causes flexibility of subjectum litis in the legislative and the regional headselestion.The method used in this research is using qualitative methods with normative juridical approach by collecting data and information of the legislative and head regional election dispute advance in literature. The results obtained in this study that the shift in legislative elections expanded not only to political parties and individuals DPD that can be subjectum litis but also those of individual candidates of political parties can be subjectum litis in the legislative election disputes. The factor that caused it is the choice of electoral system is still used to 2014 electoral system. Meanwhile, the Regional Head election disputes in general as subjectum litis are that couple candidates for Governor and Vice Governor, Regent and Vice Regent and the Mayor and Deputy Mayor. But in its development, the narrowing of the only candidates who met the threshold difference of votes that can act as an applicant. Besides narrowing, there is also an extension where Consitutional court accommodate domestic election observers were registered and accredited by the KPU / KIP can act as subjectum litis and as the applicant would be candidates in the General Election of 2010. Factors that cause the narrowing and expansion in the elections of regional heads are the will of lawmakers and the limited authority of the Consitutional court as well as the presence of a single candidate who is not predictable by lawmakers in drafting electoral laws regional head. Whereas in 2010, the expansion of subjectum litis because the Court did extensive interpretation caused by serious violations of the right to be elected (rights to be a candidate). Suggestions for lawmakers tobe more thoroughly formulate norms by looking at the existing state of society so it can bring justice and legal certainty both for the expectant couple and society.